Environmental and Cognitive Enrichment in Childhood as Protective Factors in the Adult and Aging Brain - Schoentgen, Bertrand; Gagliardi, Geoffroy; Défontaines, Bénédicte (Frontiers in Psychology, 2020)
Some recent studies have highlighted a link between a favorable childhood environment and the strengthening of neuronal resilience against the changes that occur in natural aging neurodegenerative disease. Many works have assessed the factors —both internal and external — that can contribute to delay the phenotype of an ongoing neurodegenerative brain pathology. At the crossroads of genetic, environmental and lifestyle factors, these relationships are unified by the concept of cognitive reserve (CR). This review focuses on the protective effects of maintaining this CR through the cognitive aging process, and emphasizes the most essential time in life for the development and strengthening of this CR. The in-depth study of this research shows that early stimulation with regard to social and sensory interactions, contributes to the proper development of cognitive, affective and psychosocial capacities. Childhood thus appears to be the most active phase in the development of CR, and as such we hypothesize that this constitutes the first essential period of primary prevention of pathological aging and loss of cognitive capacities. If this hypothesis is correct, early stimulation of the environment would therefore be considered as a true primary prevention and a public health issue. The earlier identification of neurodevelopmental disorders, which can affect personal and professional development across the lifespan, could therefore have longer-term impacts and provide better protection against aging.